Caenorhabditis elegans: a model to investigate oxidative stress and metal dyshomeostasis in Parkinson's disease - Chege, Patricia M.; McColl, Gawain (Frontiers in Aging Neuroscience, 2014)
Parkinson’s disease is characterized by progressive motor impairment attributed to progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Additional clinical manifestations include non-motor symptoms such as insomnia, depression, psychosis and cognitive impairment. Parkinson’s disease patients with mild cognitive impairment have an increased risk of developing dementia. The affected brain regions also show perturbed metal ion levels, primarily iron. These observations have led to speculation that metal ion dyshomeostasis plays a key role in the neuronal death of this disease. However, the mechanisms underlying this metal-associated neurodegeneration have yet to be completely elucidated. Mammalian models have traditionally been used to investigate Parkinson’s disease pathogenesis. However, alternate animal models are also being adopted, bringing to bear their respective experimental advantage. The nematode, Caenorhabditis elegans, is one such system that has well-developed genetics, is amenable to transgenesis and has relatively low associated experimental costs. C. elegans has a well characterised neuronal network that includes a simple dopaminergic system. In this review we will discuss mechanisms thought to underlie Parkinson’s disease and the use of C. elegans to investigate these processes.